2009
DOI: 10.1002/ana.21636
|View full text |Cite
|
Sign up to set email alerts
|

Early imaging correlates of subsequent motor recovery after stroke

Abstract: Objective: To determine whether functional magnetic resonance imaging activation obtained in the first few days after stroke correlates with subsequent motor recovery. Methods: Twenty-three patients with hemiparesis after first-time stroke were scanned at 2.0 Ϯ 0.9 days while performing a simple motor task. We defined recovery as the change in Fugl-Meyer score from time of scan to approximately 3 months later (90 Ϯ 8 days). We performed three different tests to assess correlations between brain activation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(79 citation statements)
references
References 39 publications
2
76
0
1
Order By: Relevance
“…This might be because of the contribution of alternate motor fiber pathways, such as corticorubrospinal and corticoreticulospinal tracts, 14 or to brain reorganization 37 and compensation. 38 Alternate strategies to capture the residual ability to recover over that provided by the proportional recovery rule include task-related brain activation using functional MRI 39,40 ; MEPs from transcranial magnetic stimulation 10 ; or a combination of methods such as clinical evaluation, transcranial magnetic stimulation, and DTI. 10,35,36 These strategies might be helpful to further refine prognostic modeling in combination with the iFNr especially in patients with severe initial deficit.…”
Section: Discussionmentioning
confidence: 99%
“…This might be because of the contribution of alternate motor fiber pathways, such as corticorubrospinal and corticoreticulospinal tracts, 14 or to brain reorganization 37 and compensation. 38 Alternate strategies to capture the residual ability to recover over that provided by the proportional recovery rule include task-related brain activation using functional MRI 39,40 ; MEPs from transcranial magnetic stimulation 10 ; or a combination of methods such as clinical evaluation, transcranial magnetic stimulation, and DTI. 10,35,36 These strategies might be helpful to further refine prognostic modeling in combination with the iFNr especially in patients with severe initial deficit.…”
Section: Discussionmentioning
confidence: 99%
“…11 At more chronic stages, enhanced negative coupling between contralesional and ipsilesional-MI is seen in patients with poorer outcome. 34 The higher the activity in those areas, the poorer the associated recovery, 3,7 suggesting that contralesional motor activity might not represent functionally relevant processes. Indeed a recent resting state stroke study using graph theory showed that stronger engagement of the contralesional hemisphere was associated with ineffective motor reorganization.…”
Section: Contralesional Motor Cortical Activity Changes After Strokementioning
confidence: 99%
“…16,17 Notably, a recent functional magnetic resonance imaging study has shown that the pattern of brain activation present in the early phase after stroke could be predictive of subsequent recovery of motor functions. 18 …”
Section: Contralateral Hemisphere Involvementmentioning
confidence: 99%